A new microwave applicator for laparoscopic and robotic liver resection. (1st January 2019) - Dimitri, Mattia; Staderini, Fabio; Brancadoro, Margherita; Frosini, Francesco; Coratti, Andrea; Capineri, Lorenzo; Corvi, Andrea; Cianchi, Fabio; Biffi Gentili, Guido
Abstract: Purpose: Bleeding from parenchyma transection during a robotic hepatic surgery remains the most critical point affecting postoperative recovery and long-term survival. Various robotic devices with different types of energies have been proposed; however, each of these lack in steerability, efficacy, or accuracy. The aim of this work is to evaluate the feasibility and performance of a new steerable microwave resection device intended for minimizing intraoperative blood loss during laparoscopic and robotic liver resections. Methods: The new device operating at 2.45 GHz was designed to accommodate the engineering constraints derived from its use for robotic surgery or laparoscopy, in which a steerable head is required and the internal cooling of forced gas or water is undesirable. The device design, analysis, and optimization were addressed using the most advanced commercial electromagnetic and thermal solvers to achieve the best results. To experimentally validate the results of the numerical analysis, many ablations were performed on a freshly explanted bovine liver by using a single device prototype with three levels of energy supplied to the tissue. During the ablation procedures, the time, temperature, and shape of the thermal lesion were recorded using thermocouples and an infra-red thermos camera. Summary: Ex vivo tests showed good agreement with the numerical simulations, demonstrating the validity of the simplifications adopted to deal with the complex phenomena involved in the extreme hyperthermia of a living tissue. The high performance, thermal reliability, and robustness of the developed device were also demonstrated along with the possibility of reducing operation time and blood loss.